2016
DOI: 10.1016/j.amsu.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery bypass grafting in South Asian patients: Impact of gender

Abstract: BackgroundOutcomes following Coronary artery bypass grafting (GABG) vary between genders, with females having a higher postoperative mortality than males. Most of the studies are on Caucasian or mixed population and it is postulated that Asian population and in particular women have higher morbidity and mortality. In this study we have compared outcomes of elective CABG in men and women of South Asian origin in terms of morbidity and mortality.MethodsFrom January 2006 to December 2012, 1970 patients underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
1
2
2
Order By: Relevance
“…We also compared the outcome of CABG with and without LIMA in the elective and urgent groups and found that CABG with LIMA is associated with reduced mortality and major morbidity in both the elective and urgent groups. Similarly, female sex is also a commonly referred factor precluding the use of IMA, however, in our study, it was not considered contraindicated despite the fact that they are at high risk of mortality [17]. In the no LIMA group, patients were of older age as compared to the LIMA group and presented with acute myocardial infarction, which was comparable with other studies [6,16].…”
Section: Discussionsupporting
confidence: 87%
“…We also compared the outcome of CABG with and without LIMA in the elective and urgent groups and found that CABG with LIMA is associated with reduced mortality and major morbidity in both the elective and urgent groups. Similarly, female sex is also a commonly referred factor precluding the use of IMA, however, in our study, it was not considered contraindicated despite the fact that they are at high risk of mortality [17]. In the no LIMA group, patients were of older age as compared to the LIMA group and presented with acute myocardial infarction, which was comparable with other studies [6,16].…”
Section: Discussionsupporting
confidence: 87%
“…The multivariate Cox regression analysis identified neurological dysfunction, renal impairment, and left ventricular dysfunction as pre-operative determinants that were independently associated with 30-day mortality after CABG. In this study, 11.8% of the subjects presented with neurological dysfunction which is higher compared with rates of 1.4%, 2.4%, 6.3%, and 6.8% in the previous studies [13], [15], [16]. Thirty-day mortality in patients of this study with neurological dysfunction was 1.9% while mortality in patients without this condition is 0.6%.…”
Section: Discussioncontrasting
confidence: 60%
“…We further note that 6.8% of our subjects presented with impaired renal function, a higher rate than those reported in the EuroSCORE, STS studies, and a study in Taiwan [12], [16]. Patients with this condition tend to have a higher incidence of three-vessel disease and involvement of the left main coronary artery.…”
Section: Discussioncontrasting
confidence: 40%
“…Females were found to have a significantly higher risk of mortality following surgery but the pattern of morbidity was comparable. [25] However, all procedures were performed under CPB and cardioplegic arrest. Women may benefit more than men from avoidance of CPB.…”
Section: Discussionmentioning
confidence: 99%